Digitization of technology in the educational physical activity model (afiksed) based on local wisdom for junior high school physical education learning - Yutri Neka Sari; Muhsana El Cintami Lanos; Putri Cicilia Kristina; Hikmah Lestari (Lambung Mangkurat University, 2026)
Physical activity is a crucial component in supporting the physical growth and character development of junior high school students, contributing to the creation of a “Golden Generation” of Indonesia. However, the shift in local wisdom values due to societal changes has negatively affected students’ engagement in physical activity. According to the National Sports Development Index, 77.12% of children aged 10-15 years fall into the low or very low physical fitness category, primarily due to insufficient physical activity and limited instructional media in Physical Education (PE) classes. This study aimed to develop and evaluate the feasibility of an innovative Educational Physical Activity (Afiksed) model, grounded in local wisdom and integrated with digital technology via an Android application. The application comprises four main menus: physical activity simulations, PE and local culture materials, learning reflection, and interactive quizzes. The study employed a Research and Development (R&D) approach through the Define, Design, and Develop stages. Needs analysis revealed that students exhibited good activeness and motor skills, yet technology use in learning remained low, while teachers required a learning model that is both varied and culturally grounded. Expert validation indicated very high feasibility across learning content (92%), basic movement skills (90%), and digital learning media (88%), with an overall validity of 90%, categorized as Very Valid. These findings indicate that the mobile-based Afiksed model is feasible for implementation and ready for field trials to evaluate its effectiveness in improving physical education learning in junior high schools. This study contributes to the field by providing a culturally relevant, technology-enhanced PE learning model that promotes student engagement, physical fitness, and learning outcomes.